2014
DOI: 10.1515/zpch-2013-0455
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Dependence of Water Microdroplet Shattering with Dual IR Lasers and Dye Sensitization

Abstract: We have used time-resolved imaging to examine the effect of incident radiation wavelength in the range 2.75–3.75 μm on the shattering of water microdroplets by single and dual lasers. Dye sensitization of microdroplets was induced by using the water-soluble dye sulforhodamine G; this enabled us to observe both the forward and backward components of fragmented droplets and splashes. Compared with employing a single IR laser, simultaneous illumination by two IR lasers can effectively compress the spatial distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Since fragmentation of covalent bonds is rarely observed in LILBID, we speak primarily of the dissociation of noncovalent bonds. The mechanism of laser energy transfer, which leads to desorption and laser-induced dissociation, are the subject of on-going research [26][27][28][29][30] . Nevertheless, past qualitative studies have shown that different amounts of laser energy transfer lead to differences in complex dissociation 12,13,31,32 .…”
Section: Openmentioning
confidence: 99%
“…Since fragmentation of covalent bonds is rarely observed in LILBID, we speak primarily of the dissociation of noncovalent bonds. The mechanism of laser energy transfer, which leads to desorption and laser-induced dissociation, are the subject of on-going research [26][27][28][29][30] . Nevertheless, past qualitative studies have shown that different amounts of laser energy transfer lead to differences in complex dissociation 12,13,31,32 .…”
Section: Openmentioning
confidence: 99%